Tres inscripciones sobre plomo de La Carencia (Turís, Valencia) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
: In this paper we present three lead Iberian inscriptions found in La Carencia (Turís, Valencia).
Keywords: La Carencia; Turís; Valencia; Iberian Epigraphy; Lead Inscriptions; Iberian language